High-resolution structure of an atypical α-phosphoglucomutase related to eukaryotic phosphomannomutases - Nogly, Przemyslaw (2015)
The first structure of a bacterial α-phosphoglucomutase with an overall fold similar to eukaryotic phosphomannomutases is reported. Unlike most α-phosphoglucomutases within the α-D-phosphohexomutase superfamily, it belongs to subclass IIb of the haloacid dehalogenase superfamily (HADSF). It catalyzes the reversible conversion of α-glucose 1-phosphate to glucose 6-phosphate. The crystal structure of α-phosphoglucomutase from Lactococcus lactis (APGM) was determined at 1.5 Å resolution and contains a sulfate and a glycerol bound at the enzyme active site that partially mimic the substrate. A dimeric form of APGM is present in the crystal and in solution, an arrangement that may be functionally relevant. The catalytic mechanism of APGM and its strict specificity towards α-glucose 1-phosphate are discussed.